2007
DOI: 10.1158/0008-5472.can-06-4471
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RAS-Mediated Transformation and Tumorigenesis by Targeting the Downstream E3 Ubiquitin Ligase Seven in Absentia Homologue

Abstract: Constitutively active RAS small GTPases promote the genesis of human cancers. An important goal in cancer biology is to identify means of countervailing activated RAS signaling to reverse malignant transformation. Oncogenic K-RAS mutations are found in virtually all pancreatic adenocarcinomas, making the RAS pathway an ideal target for therapeutic intervention. How to best contravene hyperactivated RAS signaling has remained elusive in human pancreatic cancers. Guided by the Drosophila studies, we reasoned tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(109 citation statements)
references
References 46 publications
3
106
0
Order By: Relevance
“…[45][46][47] and biomarker expression (37), the PyMT-driven breast cancer model can assist in the future to further define the various roles of Siah2 in breast cancer progression. Our findings, that the loss of Siah2 results in increased tumor perfusion through vascular normalization, are in accordance with previous work from our group and others showing that blockade of Siah substrate binding (14,15,18) and dominant negative Siah proteins (16,17) have tumor inhibiting properties in various cancer models. Siah inhibitors can be expected to inhibit several protumoral responses, in addition to the hypoxic response pathway (48), including Ras (16,17,49), estrogen receptors (50,51), and DNA damage signaling networks (13,52).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[45][46][47] and biomarker expression (37), the PyMT-driven breast cancer model can assist in the future to further define the various roles of Siah2 in breast cancer progression. Our findings, that the loss of Siah2 results in increased tumor perfusion through vascular normalization, are in accordance with previous work from our group and others showing that blockade of Siah substrate binding (14,15,18) and dominant negative Siah proteins (16,17) have tumor inhibiting properties in various cancer models. Siah inhibitors can be expected to inhibit several protumoral responses, in addition to the hypoxic response pathway (48), including Ras (16,17,49), estrogen receptors (50,51), and DNA damage signaling networks (13,52).…”
Section: Discussionsupporting
confidence: 93%
“…Previously, we described that the loss of Siah2 reduces the occurrence of aggressive neuroendocrine tumors and metastasis of prostate adenocarcinoma (14) and Siah2 is required for melanoma metastasis through Hif-1 (15). Furthermore, a dominant negative version of Siah blocks oncogenic Ras signaling, thereby reducing pancreatic and lung tumor growth (16,17). We have previously described that inhibition of Siah2 by using a high affinity blocking peptide that binds to its substrate recognition domain can reduce growth and vascular development of tumors in a syngeneic and orthotopic breast cancer mouse model (18).…”
Section: Introductionmentioning
confidence: 99%
“…Upon these findings, we speculate that downstream factors of Siah1 other than HIF1α may affect tumour progression. Siah was initially identified as a tumour suppressor gene [12], although recent studies have shown that knock-down of Siah by shRNA could significantly impede lung and pancreatic tumour growth in vitro and in vivo, indicating that expression of Siah itself promotes tumour growth [9,13,23]. Another study in breast cancer also showed that increased Siah expression was related to the aggressiveness of breast cancers [24].…”
Section: Discussionmentioning
confidence: 99%
“…The function of Siah in cancer progression was first investigated in pancreatic cancer. In human pancreatic cancer cells, overexpression of both mutated Siah1 and Siah2 was found to cause growth arrest [28] . In addition, overexpression of Siah1 arrested the growth of hepatoma cells [29] .…”
Section: Function Of Siah As a Tumor Sup-pressor Protein And Its Rolementioning
confidence: 99%